Quantitative Analysis of Berberidis Cortex via Quantitative Analysis of Multicomponents by Single Marker (QAMS) Combined with Fingerprint and Chemometrics Methods - Yuting Su; Yao Peng; Jie Ren; Shangjie Wu; Si Lei; Fei Peng; Zhina Sun; Xiuqing He; Juan Li; Shunxiang Li (Journal of Analytical Methods in Chemistry)
Berberidis Cortex is rich in alkaloids, and many of them have antibacterial, anti-inflammatory, and hypoglycemic activities. However, few research studies have focused on the quantitative analysis of multiple components from Berberidis Cortex. In this study, a new quality evaluation strategy for Berberidis Cortex was developed and validated by high-performance liquid chromatography (HPLC), which involved single marker, fingerprint, and stoichiometric methods. Using berberine hydrochloride as an internal reference, the relative correction factors of palmatine hydrochloride, magnoline, and jatrorrhizine hydrochloride were 2.4537, 0.9783, and 1.0035, respectively, and their durabilities were also well performed. In addition, both methods mentioned above were used to compare the mass fractions of four isoquinoline alkaloids in ten batches of Berberidis Cortex from different origins. These results indicated that the approach applied in this study was accurate and feasible. The fingerprints of these ten batches of Berberidis Cortex were established, and eleven components were identified with the similarity greater than 0.993. Both cluster and principal component analysis were carried out based on the peak area of these components, the results demonstrated that these ten batches of Berberidis Cortex were divided into two groups and the distribution of the medicinal material was basically consistent. Therefore, quantitative analysis of multicomponents by single marker (QAMS) can be widely used in the quality control of Berberidis Cortex as theoretical basis.